Alberta's Friends of Medicare seek acceptance in a sceptical province - Gray, Charlotte (1995)
Alberta has probably made the strongest efforts of any province to reduce its health care costs. Leading the opposition to the cuts is an organization called the Friends of Medicare, a motley mix of underfinanced public-interest groups that is fighting to stop the province from sliding toward a two-tier health care system. “Alberta is dragging the rest of the country down to a two-tier system,” says Dr. Hubert Kammerer, a family physician who serves as a spokesperson for the organization. He warns that many Albertans worry that their health care system is deteriorating.